Analisis Pengaruh Beban Kerja dan Shift Kerja Terhadap Stres Kerja Karyawan Operator pada PT. XYZ - Zulfa, Aqillah Nabila; Lukman, Lukman; Andrianti, Irma (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
XYZ is a company engaged in the processing of oil and gas, serving as a crude oil storage facility. The issue concerns the workload and work shifts of the employees. This study aims to determine whether there is an impact of workload and work shifts on operator employees. The method used in this study is quantitative. The research results show that the workload has a significant effect on employee work stress, as obtained from the t-test with a significant value of 0.022 < 0.05, which means that the workload has a significant partial effect on work stress. Meanwhile, work shifts do not have a significant effect on employee work stress, as obtained from the t-test with a significant value of 0.196 > 0.05, meaning work shifts do not have a significant partial effect on work stress. This is because the majority of operators in the company have worked for more than 1 year, which means that operators have already adapted to the shift changes. This study is expected to contribute to reducing the factors that can cause work stress among operator employees. Improvement recommendations are proposed to increase unit effectiveness, such as establishing a maintenance schedule, checking and replacing components, and operator training. It is hoped that this research can contribute to increasing the effectiveness of unit use and company productivity.